Evaluation of Daily Duty Plan of Secondary School Heads in Perspective of TASPA Model - Tasleem Ullah, Iftikhar Ahmed Baig, (PJE, 2023)
This research provided the theoretical orientation for examining school heads daily duty schedule/plan. The research provided that could help to evaluate and validate the proposed School Heads Daily Duty Plan. Objectives of study were to develop and validate TASPA Model Daily Duty Plan for Secondary School Heads. It was a descriptive research which aimed to assess the impact of Time, Activity, Strategy, Progress, Assessment Oriented TASPA Model designed as School Heads Daily Duty Plan. Population of the study consisted of all public sector secondary School Heads in Punjab. The accessible involved population was 270 Secondary School Heads in nine districts of three divisions in central Punjab. Randomly three districts from each division and three tehsils from each district were selected for the study. Questionnaire was used as an instrument of the study. Data were categorized according to five point Likert scale.t-test was applied. Conclusion was the finalized validated TASPA Model based Daily Duty Plan (DDP) for the Secondary School Heads as an end-product of study. It was a validated tool for the secondary school educational leadership for supervising the institutions in an efficient, productive and useful manner on daily basis.